A study of lateral Schottky contacts in WSe2 and MoS2 field effect transistors using scanning photocurrent microscopy. Issue 38 (9th September 2015) - Yi, Ya; Wu, Changming; Liu, Hongchao; Zeng, Jiali; He, Hongtao; Wang, Jiannong
Abstract : A scanning photocurrent microscopy method is applied to study the lateral expansion of depletion regions at the metal/2D TMDC Schottky contacts with different gate and drain biases. Abstract : Schottky contacts, formed at metal/semiconductor interfaces, always have a large impact on the performance of field-effect transistors (FETs). Here, we report the experimental studies of Schottky contacts in two-dimensional (2D) transition metal dichalcogenide (TMDC) FET devices. We use scanning photocurrent microscopy (SPCM) to directly probe the spatial distribution of the in-plane lateral Schottky depletion regions at the metal/2D-TMDC interfaces. The laser incident position dependent and the gate voltage tunable polarity and magnitude of the short-circuit photocurrent reveal the existence of the in-plane Schottky depletion region laterally extending away from the metal contact edges along the channel. This lateral depletion region length is estimated to be around several microns and can be effectively tuned by the gate and drain–source biases. Our results solidify the importance of lateral Schottky depletion regions in the photoresponse of 2D TMDC optoelectronic devices.